A dangerous cough. (1st March 2013) - Chitnis, Abhishek Rajeev
Abstract : Patient X is a 48-year-old retired potteries worker who presented to his general practitioner (GP) with a non-productive cough, which had lasted over 1 month, and it was a television advert that he had seen that prompted him to visit his doctor. A cough is the most common presenting complaint for patients when they visit their GP and when considering differential diagnoses it is important to look at a patient's medical, drug and social history. It would have been easy for the GP to dismiss the cough as an exacerbation of the patient's asthma based on his medical history, but on further questioning into the patient's social history an emergency chest x-ray was ordered, which later revealed a bronchial carcinoma. This case highlights the importance of the media in healthcare advertising and describes how a fairly innocent presentation can later turn out to be a more sinister pathology.